Caffeine increases exercise performance, maximal oxygen uptake, and oxygen deficit in elite male endurance athletes - Stadheim, H. K.; Stensrud, T.; Brage, S.; Jensen, J. (Medicine & Science in Sports & Exercise, 2021)
Caffeine increases endurance performance, but the physiological mechanisms improving high-intensity endurance capacity are not well characterized. Purpose: The aims of the present study were to test the hypothesis that caffeine increases maximal oxygen uptake (V.O2max) and to characterize the physiological mechanisms underpinning improved high-intensity endurance capacity. Methods: Twenty-three elite endurance-trained male athletes were tested twice with and twice without caffeine (four tests) in a randomized, double-blinded, and placebo-controlled study with crossover design. Caffeine (4.5 mg/kg) or placebo was consumed 45 min before standardized warm-up. Time to exhaustion during an incremental test (running 10.5° incline, start speed 10.0 km/h, and 0.5 km/h increase in speed every 30 s) determined performance. Oxygen uptake was measured continuously to determine V.O2max and O2 deficit was calculated. Results : Caffeine increased time to exhaustion from 355 ± 41 to 375 ± 41 s (Delta19.4 ± 16.5 s; P < 0.001). Importantly, caffeine increased V.O2max from 75.8 ± 5.6 to 76.7 ± 6.0 mL/kg·min (Delta 0.9 ± 1.7 mL/kg·min; P < 0.003). Caffeine increased maximal heart rate (HRpeak) and ventilation (VEpeak). Caffeine increased O2 deficit from 63.1 ± 18.2 to 69.5 ± 17.5 mL/kg (P < 0.02) and blood lactate compared with placebo. The increase in time to exhaustion after caffeine ingestion was reduced to 11.7 s after adjustment for the increase in V.O2max. Caffeine did not significantly increase V.O2max after adjustment for VEpeak and HRpeak. Adjustment for O2 deficit and lactate explained 6.2 s of the caffeine-induced increase in time to exhaustion. The increase in V.O2max, VE, HR, O2 deficit, and lactate explained 63% of the increased performance after caffeine intake. Conclusion: Caffeine increased V.O2max in elite athletes, which contributed to improvement in high-intensity endurance performance. Increases in O2 deficit and lactate also contributed to the caffeine-induced improvement in endurance performance.